INCIDENCE OF BROODER PNEUMONIA AND GENOTYPING ASPERGILLUS FUMIGATUS IN BROILER FARMS IN SULAIMNAIYAH - Mahmood, B. A.; Al-Jaff, B. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Brooder pneumonia is aspergillosis occurs in chicks caused by Aspergillus fumigatus during the first-week post-hatching. It has not been confirmed yet that all A. fumigatus strains cause brooder pneumonia or it restricted to pathogenic strains. From an outbreak included 28 broiler farms in Sulaimaniyah province, 575 dead and sick chicks were randomly selected, diagnosed clinically, histopathologically, and by post-mortem isolation of A. fumigatus, among them 321 chicks were confirmed to be infected by aspergillosis with incidence rate of (57.5 %). Twenty eight clinical isolates of A. fumigatus along with 15 farm environment isolates represented all the farms were subjected to genotyping through (CA)n and (CACCAC)n short tandem microsatellite DNA repeats. All clinical and environmental isolates were highly polymorphic except two clinical isolates from two different farms which were with the same genotype. It could be concluded that all A. fumigatus strains are potential causative agents of brooder pneumonia.